Coating cortical bone allografts with periosteum-mimetic scaffolds made of chitosan, trimethyl chitosan, and heparin. (20th May 2015) - Romero, Raimundo; Chubb, Laura; Travers, John K.; Gonzales, Timothy R.; Ehrhart, Nicole P.; Kipper, Matt J.
Highlights: Novel periosteum-mimicking scaffolds were made from chitosan, trimethyl chitosan and heparin. This is the first report of chitosan nanofibers and freeze-dried scaffolds directly deposited onto bone. Adipose-derived stem cells cultured on scaffolds proliferate and express an osteoprogenitor phenotype for up to 21 days. Periosteum-like scaffolds on bone allografts could improve graft integration by mimicking bone autograft healing. Abstract: Bone allografts have very limited healing leading to high rates of failure from non-union, fracture, and infection. The limited healing of bone allografts is due in large part to devitalization and removal of the periosteum, which removes osteogenic cells and osteoinductive signals. Here we report techniques for directly coating cortical bone with tissue scaffolds, and evaluate the scaffolds' capacity to support osteoprogenitor cells. Three types of coatings are investigated: N, N, N -trimethyl chitosan–heparin polyelectrolyte multilayers, freeze-dried porous chitosan foam coatings, and electrospun chitosan nanofibers. The freeze-dried and electrospun scaffolds are also further modified with polyelectrolyte multilayers. All of the scaffolds are durable to subsequent aqueous processing, and are cytocompatible with adipose-derived stem cells. Alkaline phosphatase and receptor activator of nuclear factor kappa-B ligand expression at days 7 and 21 suggest that these scaffolds support an osteoprogenitor phenotype. These scaffolds could serve as periosteum mimics, deliver osteoprogenitor cells, and improve bone allograft healing.